A Polysaccharide Produced by Lactococcus lactis subsp. lactis YZ1 Isolated from Traditional Indonesian Fermented Milk, "Dadih" - Yusdar Zakaria (Jurnal Agripet, 2000)
ABSTRACT.Lactococcus lactis subsp. Lactis YZI was isolated from M17 agar in which diluted Dadih was poured and incubated at 30 0C for 48 h. Taxonomix properties of the isolate were examined according to Bergeys Manual of Systematic Bacteriologi and Manual for Identification of Medical Bacteria. The isolation of polysaccharide from the precipitant was performed on an ion-exchange chromatography. The result showed that the polysaccharides produced by Lactococus lactis subsp. lactis YZI were neutral sugar (unadsorbrd fraction) and glycoconjugated (absorbed fraction). The neutral sugar had molecular weight of 10,000 and 20,000 with and -glycoside linkage. The monosaccharide composition was mannose, glucose and galactose with a molar ratio of 1 :1,5 : 4,9.